Circulating Endocannabinoids as Diagnostic Markers of Canine Chronic Enteropathies: A Pilot Study - Febo, Elettra; Crisi, Paolo Emidio; Oddi, Sergio; Pietra, Marco; Galiazzo, Giorgia; Piscitelli, Fabiana; Gramenzi, Alessandro; Prinzio, Roberta Di; Di Tommaso, Morena; Bernabò, Nicola; Bisogno, Tiziana; Maccarrone, Mauro; et al. (Frontiers in Veterinary Science, 2021)
Chronic enteropathies (CEs) in dogs, according to the treatment response to consecutive trials, are classified as food-responsive (FRE), antibiotic-responsive (ARE), and immunosuppressive-responsive (IRE) enteropathy. In addition to this classification, dogs with loss of protein across the gut are grouped as protein-losing enteropathy (PLE). At present, the diagnosis of CEs is time-consuming, costly and sometimes invasive, also because non-invasive biomarkers with high sensitivity and specificity are not yet available. Therefore, this study aimed at assessing the levels of circulating endocannabinoids in plasma as potential diagnostic markers of canine CEs. Thirty-three dogs with primary chronic gastrointestinal signs presented to Veterinary Teaching Hospitals of Teramo and Bologna (Italy) were prospectively enrolled in the study, and 30 healthy dogs were included as a control group. Plasma levels of N-arachidonoylethanolamine (AEA), 2-arachidonoylglycerol (2-AG), N-palmitoylethanolamine (PEA), and N-oleoylethanolamine (OEA) were measured at the time of the first visit in dogs with different CEs, as well as in healthy subjects. Plasma levels of 2-AG (p = 0.001) and PEA (p = 0.008) were increased in canine CEs compared to healthy dogs. In particular, PEA levels were increased in the FRE group compared to healthy dogs (p = 0.04), while 2-AG was higher in IRE than in healthy dogs (p = 0.0001). Dogs affected by FRE also showed decreased 2-AG (p = 0.0001) and increased OEA levels (p = 0.0018) compared to IRE dogs. Moreover, dogs with PLE showed increased 2-AG (p = 0.033) and decreased AEA (p = 0.035), OEA (p = 0.016) and PEA (p = 0.023) levels, when compared to dogs affected by CEs without loss of proteins. The areas under ROC curves for circulating 2-AG (0.91; 95% confidence interval [CI], 0.79-1.03) and OEA (0.81; 95% CI, 0.65-0.97) showed a good accuracy in distinguishing the different forms of CEs under study (FRE, ARE and IRE), at the time of the first visit. The present study demonstrated that endocannabinoid signalling is altered in canine CEs, and that CE subtypes showed distinct profiles of 2-AG, PEA and OEA plasma levels, suggesting that these circulating bioactive lipids might have the potential to become candidate biomarkers for canine CEs.